The influence of quality of work life and job satisfaction on job performance in BAPPEDA of Bengkulu province - Fanny Putra Utama; Fahrudin JS Pareke (Institute of Computer Science (IOCS), 2024)
This study aims to examine the effect of quality of work life and job satisfaction on job performance at BAPPEDA. This research uses quantitative methods with a survey design. The research sample amounted to 74 employees of Bappeda Bengkulu Province. Data were collected using a questionnaire adapted from indicators of quality of work life, job satisfaction, and job performance. Data were analyzed using multiple linear regression analysis. The results showed that quality of work life and job satisfaction have a positive and significant effect on job performance in Bappeda Bengkulu Province. The coefficient of determination (R2) shows that 58.9% of job performance variance can be explained by the quality of work life and job satisfaction variables. This means that the higher the quality of work life and job satisfaction of employees, the higher their job performance